Universality of indeterminate growth in lizards rejected: the micro-CT reveals contrasting timing of growth cartilage persistence in iguanas, agamas, and chameleons - Frýdlová, Petra; Mrzílková, Jana; Šeremeta, Martin; Křemen, Jan; Dudák, Jan; Žemlička, Jan; Němec, Pavel; Velenský, Petr; Moravec, Jiří; Koleška, Daniel; Zahradníčková, Veronika; Jirásek, Tomáš; et al. (Scientific reports, 2019)
Squamate reptiles are considered to exhibit indeterminate growth. Nevertheless, current literature disputes the available definitions of this growth type, presents new theoretical models, and questions its universality in cold-blooded vertebrates. We have followed up on our previous research employing micro-CT to explore growth plate cartilage (GPC) in the epiphysis of long bones, which is responsible for longitudinal skeletal growth by the endochondral ossification process. We focused on numerous and highly diversified group of the Iguania clade comprising Acrodonta (agamas and chameleons) and Pleurodonta ("iguanas"). We recorded the absence of GPC in most of the examined adult Pleurodonta specimens and interpret it as an irreversible arrest of skeletal growth. This finding clearly rejects the universality of indeterminate growth in lizards. On the other hand, we found apparent GPC preservation in most of the adult specimens belonging to Acrodonta. This suggests a preserved ability to continue body growth throughout most of their life. We discuss the uncovered disparity between Acrodonta and Pleurodonta and emphasize the importance of GPC degradation timing.
Keywords: fylogeneze; Animals; Lizards; chrupavka; rentgenová mikrotomografie; Cartilage; Phylogeny; růstová ploténka; ještěři; Growth Plate; zvířata; X-Ray Microtomography